The introduction of radioactive seed localisation improves the oncological outcome of image guided breast conservation surgery. (December 2017) - Pieri, A.; Milligan, R.; Critchley, A.; O'Donoghue, J.M.; Sibal, N.; Peace, R.; Petrides, G.; Howitt, R.; Nicholson, S.; Cain, H.
Abstract: Introduction: Radioactive seed localisation (RSL) has become increasingly popular for localisation of non-palpable breast tumours. This is largely due to advantages it offers in terms of practicality and convenience when compared to guide wire localisation (WL). This institute switched from using WL to RSL in September 2014. The primary aim was to assess whether this change improved the accuracy of excision with regards to inadequate margin rates and weight of excision specimens. The secondary aim was to establish whether there is a "learning curve" associated with RSL technique. Methods: Retrospective data collection was performed for 333 consecutive cases of unifocal non-palpable invasive breast cancers undergoing excision with WL or RSL. An inadequate margin was defined as tumour <1 mm from an inked radial margin. Patient demographics, tumour characteristics and clinical outcomes were compared between WL and RSL cases. Results: 100 WL and 233 RSL cases were included. Patient demographics and tumour characteristics were similar for both groups. Inadequate margin rates were 18% with WL and 8.6% with RSL (p = 0.013). Median specimen weights were 33.3 g with WL and 28.7 g with RSL (p = 0.014). Subdividing the RSL group into the first 100 cases performed (RSL1) and the subsequent 133 cases (RSL2), inadequate margin rates were 13.0% and 5.3% respectively (p = 0.037). Mean specimen weights were similar. Conclusion: Switching from WL to RSL results in a significant reduction in both inadequate margin rates and specimen weights. A procedure-specific learning curve is present on first implementation of RSL and following this, inadequate margin rates are further reduced. Highlights: Implementing radioactive seed localisation leads to a reduced positive margin rate. Average specimen weight is reduced with seed localisation. A procedure learning-curve is seen when switching from wire to seed localisation.